2016
DOI: 10.1016/j.eurpsy.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

BDNF Val66Met and clinical response to antipsychotic drugs: A systematic review and meta-analysis

Abstract: The present meta-analysis excludes a clinically relevant effect of BDNF Val66Met on antipsychotic drug response per se. Nevertheless, further investigation is still needed to clarify in well-designed, large sample-based studies, the impact of BDNF haplotypes containing the Val66Met polymorphism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
0
8
0
1
Order By: Relevance
“…One recent schizophrenia study utilized clinically assigned clozapine therapy as a proxy for treatment resistance (by comparing clozapine-treated patients to those who have never been prescribed clozapine) and found that PRS was significantly higher in clozapine patients than in non-clozapine patients(17), although another study failed to replicate the finding (18). However, both were cross-sectional studies that can be affected by ascertainment bias and inaccuracies of classification; for example, a similar cross-sectional study providing evidence for a pharmacogenetic role for the BDNF Val66Met variant(19) was not supported by subsequent longitudinal studies conducted in the context of clinical trials(20). Furthermore, PRS may have additional advantages in clinical prediction because it is a continuous variable that can have different cutoffs that maximize predictive power, whereas the candidate gene approach can compare only carriers to non-carriers.…”
Section: Introductionmentioning
confidence: 99%
“…One recent schizophrenia study utilized clinically assigned clozapine therapy as a proxy for treatment resistance (by comparing clozapine-treated patients to those who have never been prescribed clozapine) and found that PRS was significantly higher in clozapine patients than in non-clozapine patients(17), although another study failed to replicate the finding (18). However, both were cross-sectional studies that can be affected by ascertainment bias and inaccuracies of classification; for example, a similar cross-sectional study providing evidence for a pharmacogenetic role for the BDNF Val66Met variant(19) was not supported by subsequent longitudinal studies conducted in the context of clinical trials(20). Furthermore, PRS may have additional advantages in clinical prediction because it is a continuous variable that can have different cutoffs that maximize predictive power, whereas the candidate gene approach can compare only carriers to non-carriers.…”
Section: Introductionmentioning
confidence: 99%
“…They meta-analyzed the PGx variants in association with an antipsychotic response (11 meta-analysis studies; 20 variants across 10 genes), antipsychotic-induced weight/BMI gain (eight meta-analysis studies; 38 variants across 20 genes and four phenotypes of CYP2D6 ), metabolic syndrome (one meta-analysis study; three variants in HTR2C ), antipsychotic-related prolactin levels (two meta-analysis studies; two variants in DRD2 and four phenotypes of CYP2D6 ), antipsychotic-induced tardive dyskinesia (four meta-analysis studies; five variants across four genes), clozapine-induced agranulocytosis (one meta-analysis study; 13 PGx variants across nine genes), and plasma levels of antipsychotic drugs (three meta-analysis studies; two PGx variants in CYP1A2 , four phenotypes of CYP2D6 and three phenotypes of CYP2C19 ) ( Supplementary Tables S1 and S2 ). For treatment response, three meta-analysis studies reported in a mixed population, Caucasians and Asians separately [ 40 , 41 , 42 ]; one meta-analysis study reported in a mixed population and Caucasians [ 31 ]; six meta-analysis studies reported in mixed populations only [ 34 , 43 , 44 , 45 , 46 , 47 ]; one meta-analysis study reported in Asians [ 48 ]. For antipsychotic-induced weight/BMI gain, two meta-analysis studies reported in a mixed population, Caucasians and Asians separately [ 49 , 50 ]; two meta-analysis studies reported in a mixed population and Asians separately [ 51 , 52 ]; three meta-analysis studies reported in mixed population only [ 35 , 53 , 54 ]; one meta-analysis study did not state the ethnicity of the population [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Earlier findings attributed the response to antipsychotics to the presence of the BDNF Val66Met polymorphism (Nikolac Perkovic et al 2014). However, this relationship was questioned in a recent meta-analysis (Cargnin et al 2016). Nevertheless, although no n−3 PUFA supplementation studies assessing neurotrophin profile have been conducted in schizophrenia patients, the animal studies described strongly support the results of the present study, which indicate increases in BDNF peripheral levels after n−3 PUFA supplementation in first-episode schizophrenia patients.…”
Section: Discussionmentioning
confidence: 99%